Studi Komparasi Pendidikan Karakter di Indonesia dan Jepang - Alifah Aulia Nurfadhilah; Febrianti Astutiningsih; Taufik Muhtarom (Journal Innovation In Education, 2024)
This research aims to analyze the comparison of the implementation and cultivation of character education between Indonesia and Japan. The focus of the study is on approaches and applications in formal and non-formal education as well as the influence of the community environment on character education in two countries. The research method used is a qualitative research method using a library approach or better known as library research. The data sources for this research come from research results, government policies related to character education in these two countries. The research results explain that the basis of character education in Indonesia is state ideology, customs and culture, religious values, government rules and policies. Likewise, in Japan the basis for character education is cultural values, state ideology and government policy regulations. Approaches to character education in Indonesia include the value instillation approach, learning approach, example, and habituation. Whereas in Japan, among other things, the approach tends to be habituation, for the Japanese people, character is not taught but is used to it. The influence of community support on character education in Indonesia and Japan greatly influences the ethics produced by students.